2023
DOI: 10.3390/nu15102375
|View full text |Cite
|
Sign up to set email alerts
|

The ALINFA Intervention Improves Diet Quality and Nutritional Status in Children 6 to 12 Years Old

Abstract: The study aimed to evaluate the efficacy of a new nutritional intervention, focused on improving the quality of the diet in children aged 6 to 12 years. A 2-month parallel, controlled randomized trial was conducted in the Spanish child population. The children were randomized to ALINFA nutritional intervention, which consisted of a normocaloric diet that incorporates products, ready-to-eat meals and healthy recipes specifically designed for the study, or a control group, which received the usual advice on heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 77 publications
(96 reference statements)
0
20
0
Order By: Relevance
“…Longer durations have been associated with positive outcomes [19], with research suggesting a minimum of 40-50 classroom hours [45], six months [46], or even 12 months for longterm changes in children's dietary habits and attitudes [19]. Nevertheless, several studies, including ours, have demonstrated that even brief interventions that can easily be incorporated into school curriculums can impact nutritional knowledge [19,21] and dietary behaviors [13,20,21]. Identifying the ideal duration should involve comprehensive planning considering the desired effect, cost-effectiveness, volume of material, and likelihood of achieving beneficial outcomes [47].…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Longer durations have been associated with positive outcomes [19], with research suggesting a minimum of 40-50 classroom hours [45], six months [46], or even 12 months for longterm changes in children's dietary habits and attitudes [19]. Nevertheless, several studies, including ours, have demonstrated that even brief interventions that can easily be incorporated into school curriculums can impact nutritional knowledge [19,21] and dietary behaviors [13,20,21]. Identifying the ideal duration should involve comprehensive planning considering the desired effect, cost-effectiveness, volume of material, and likelihood of achieving beneficial outcomes [47].…”
Section: Discussionmentioning
confidence: 79%
“…Nevertheless, the role of parental involvement in education should not be undermined. Many interventions call for the involvement of parents in the educational process [13,21]. Parental involvement is often achieved with homework assignments [12,19,57], active participation in educational activities [14,21], training sessions curated specifically for the parents [21], newsletters [58], and many more activities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In school-aged children, interventions taking a rather innovative approach have been conducted, such as school-based gardening, 93 gamification strategy to nutrition and physical activity, 94 or interventions delivered by class-room teachers. 95 However, only few studies conducted in school-aged children have found intervention effects (for example, other works [94][95][96] ), and the majority of studies have shown no effects of the intervention (for example, previous studies 93,[97][98][99][100][101][102][103] ).…”
Section: Main Findings From Updated Reviewmentioning
confidence: 99%